1973
DOI: 10.1021/ja00788a007
|View full text |Cite
|
Sign up to set email alerts
|

Metastable ion characteristics. XXII. Collisional activation spectra of organic ions

Abstract: have similar probability of occurring. Since h'-f*y-h\y*y are all differentiable in a totally symmetric environment, detailed nmr line shape analysis may allow distinction between "helical" movement of the aliene ligand and isomerization via an intermediate configuration having coplanar allenyl methyl groups. Note that this final example has been simplified by assuming that rapid " -rotation" about the metalallene band does not occur.Should such rotation in fact occur, the distinction will be impossible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
71
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 329 publications
(74 citation statements)
references
References 1 publication
(1 reference statement)
3
71
0
Order By: Relevance
“…Nevertheless, the obtained tandem mass spectra can look remarkably different. Although the structure elucidation potential of CID was early recognized [19], the setup of ESI-MS/MS libraries was hampered by lacking reproducibility. This article provides comparable ion trap and triple quadrupole MS/MS data of all discussed substances.…”
mentioning
confidence: 99%
“…Nevertheless, the obtained tandem mass spectra can look remarkably different. Although the structure elucidation potential of CID was early recognized [19], the setup of ESI-MS/MS libraries was hampered by lacking reproducibility. This article provides comparable ion trap and triple quadrupole MS/MS data of all discussed substances.…”
mentioning
confidence: 99%
“…It has been claimed [5] that a unique advantage of CID spectra for structure determination is their virtual insensitivity to ion internal energy, if the peaks resulting from low activation energy pathways are ignored. The CID spectra of precursor ions of the same structure formed with different internal energies will have the same relative abundances within statistical error, if that assumption is valid.…”
Section: Fragmentation Efficiency/he-cidmentioning
confidence: 99%
“…There are limited publications on the role of precollisional internal energy on CID spectra and they show conflicting results. Some studies indicate that precursor ion internal energy has a negligible effect on the CID spectrum, except for product ions formed through processes with the lowest activation energy [5][6][7][8]. In contrast, other studies indicate that CID spectra can be highly dependent on initial energy of the precursor ion and/or angular momentum [9 -12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11 A subsequent survey of the 70 and 12 eV electron impact (EI) ionisation mass spectra of numerous alkenyl ethers C m H 2m -1 OCH 3 (m = 3-6) indicated that several mechanisms operate for alkyl radical elimination from these C n H 2n O +• • species. 12 Extension of this work to encompass determination of the structure of the fragment ions produced by alkyl radical loss by analysis of collision-induced dissociation (CID) 13 mass spectra established that hydrogen transfers and occasional skeletal isomerisations allow groups attached to either carbon atom of the double bond to be lost. 14 15 because it terminates at a radical centre of a DI, followed by γ-cleavage of the resultant ionised enol ether.…”
Section: Introductionmentioning
confidence: 99%